CORRELATION AND PATH COEFFICIENT ANALYSIS OF YIELD COMPONENTS IN AEROBIC RICE (ORYZA SATIVA L.) - CHANDAN KUMAR; NILANJAYA (The Bioscan, 2014)
A study of interrelationship and cause-effect analysis of grain yield and its component traits was carried out using thirty aerobic rice genotypes. The results indicated that relative water content (0.528), chlorophyll content (0.495), root length (0.478), panicle per plant (0.437), 1000 grain weight (0.366), grains per panicle (0.355), spikelet fertility (0.372), root volume (0.256) showed significant and positive association with grain yield per plant. Path analysis revealed that chlorophyll content, tillers per plant, panicles per plant, root volume, grains per panicle and 1000 grain weight were the major contributor of grain yield per plant and these important plant traits must be taken into consideration when any breeding program for higher paddy yield in rice under aerobic condition is to be planned.